Optimalisasi Rute Terpendek Pengiriman Hewan Qurban Dengan Penerapan Algoritma Djikstra Pada UD Ridho, Bekasi - Ridho Al-Rafiq, Muhammad; Handayani, Dwipa Handayani (Jejaring Penelitian dan Pengabdian Masyarakat (JPPM), 2025)
This research aims to optimize the shortest route for sending sacrificial animals to UD Ridho in Bekasi by applying the Djikstra algorithm. In the sacrificial animal delivery industry, efficient route selection is very important to ensure fast delivery times and low operational costs. Djikstra's algorithm, which is known as one of the most popular graph algorithms for finding the shortest path, is used in this study to calculate the best delivery route. This research began with modeling a delivery route network involving main delivery points in Bekasi. Data regarding the distance between points is collected and entered into the system for analysis using the Djikstra algorithm. The results of implementing this algorithm are compared with the delivery routes currently used by UD Ridho. The research results show that using the Djikstra algorithm can reduce the total distance traveled and delivery time significantly compared to the previously used route method. Thus, applying the Djikstra algorithm to the sacrificial animal delivery route at UD Ridho can increase operational efficiency and reduce delivery costs.